2012
DOI: 10.4014/jmb.1201.01016
|View full text |Cite
|
Sign up to set email alerts
|

Development of Monacolin K-Enriched Ganghwayakssuk (Artemisia princeps Pamp.) by Fermentation with Monascus pilosus

Abstract: Monacolin K-enriched ganghwayakssuk (Artemisia princeps Pamp.) was developed by fermentation with Monascus sp. Among the 15 Monascus spp. isolated previously from Monascus fermentation products, Monascus pilosus KMU108 produced 2,219 mg/kg of monacolin K during ganghwayakssuk fermentation with no detectable citrinin. The optimum concentrations of ganghwayakssuk and glucose determined from the response surface methodology (RSM) design were 2.2% and 3.8%, respectively. By applying these conditions, the monacolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…contains vitamins A, B 1 , B 2 , and C, various minerals, and essential oils, as well as flavonoids (D.S. Lee & Lee, ). Many diseases resulting from free radicals, including atherosclerosis, cardiovascular diseases, tumors, Parkinson's disease, and Alzheimer's disease, are prevented by antioxidants, such as flavonoids, vitamin C, and phenolic acids (Kazimierczak, Hallmann, Kazimierczyk, Sokołowska, & Rembiałkowska, ).…”
Section: Resultsmentioning
confidence: 99%
“…contains vitamins A, B 1 , B 2 , and C, various minerals, and essential oils, as well as flavonoids (D.S. Lee & Lee, ). Many diseases resulting from free radicals, including atherosclerosis, cardiovascular diseases, tumors, Parkinson's disease, and Alzheimer's disease, are prevented by antioxidants, such as flavonoids, vitamin C, and phenolic acids (Kazimierczak, Hallmann, Kazimierczyk, Sokołowska, & Rembiałkowska, ).…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies, the synthesis of Monascus metabolites is affected by the components of the culture medium. Lee and Lee found that the content of citrinin was obviously different with different culture medium and that the content of monacolin K was obviously increased during fermentation with Monascus using ganghwayakssuk as culture medium . Zhou et al found that citrinin was not present in corn hydrolysate medium used for fermentation with Monascus .…”
Section: Discussionmentioning
confidence: 99%
“…Lee and Lee found that the content of citrinin was obviously different with different culture medium and that the content of monacolin K was obviously increased during fermentation with Monascus using ganghwayakssuk as culture medium. 34 Zhou et al found that citrinin was not present in corn hydrolysate medium used for fermentation with Monascus. 35 Recently, some studies reported that mycotoxins were inhibited by polyphenol and flavonoid compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Monacolin K was quantified by HPLC as described previously [10,15]. Briefly, 2 g of freeze-dried MFR was extracted with 10 ml of 30% acetonitrile, 30% methanol, and 40% water (0.1% phosphoric acid) in a 45 ml centrifuge tube by stirring at 150 rpm in a water bath (30 o C) for 60 min.…”
Section: Measurement Of Monacolin K Pigments and Antioxidative Actimentioning
confidence: 99%
“…Recently, substrates besides rice, including garlic, dioscorea, red ginseng, and soybean, have been used to prepare Monascus-fermented products (reviewed in [13]). For example, monacolin K-enriched mugwort is developed by fermentation with Monascus pilosus [15]. Because Monascus species produce a wide range of bioactive compounds, Monascus-fermented products may contain other bioactive compounds in addition to the intrinsic ones.…”
Section: Introductionmentioning
confidence: 99%